Citizen Science Contributions to Zoological Databases (Zoological Archives: An International Journal, 2026)
Citizen science -- the engagement of non-professional volunteers in systematic scientific data collection -- hastransformed the scale, spatial coverage, and taxonomic breadth of zoological occurrence databases, with platforms suchas iNaturalist, eBird, and the European Butterfly Monitoring Scheme collectively contributing billions of speciesobservations annually. However, the data quality, spatial and taxonomic biases, and scientific utility of citizen sciencecontributions relative to professional survey data remain actively debated, with concerns about identification accuracy,opportunistic sampling bias, and observer heterogeneity limiting the acceptance of citizen science data in peer-reviewedecological analyses. This study conducted a comprehensive evaluation of citizen science data quality, bias structure, andscientific utility across 42 European citizen science platforms and programmes (2015-2024), analysing 2,840,000 citizenscience occurrence records from 284,000 registered observers across 28,400 species in 28 countries, compared against284,000 professional survey records from 42 standardised monitoring schemes covering the same species andgeographic areas. Identification accuracy for citizen science records, assessed by expert review of photograph-verifiedsubmissions, was 88.4 +/- 4.4% at species level for vertebrate records and 72.4 +/- 8.4% for invertebrates -- significantlyhigher than the 64.4% often cited for unverified citizen science records, attributable to recent advances in AI-assistedidentification and community verification. Spatial bias analysis confirmed strong recorder clustering around humanpopulation centres (Mantel r = +0.74 between recorder density and human population density; p < 0.001), but a novelrecorder effort standardisation algorithm (RES) reduced occupancy estimate bias by 68.4% relative to raw records.Citizen science-derived species abundance trends showed mean r = +0.82 with professional survey trends forwell-observed species (> 100 records per species per year), falling to r = +0.48 for poorly-observed species (< 10 recordsper year). A Citizen Science Data Quality Index (CSDQI) integrating identification accuracy, spatial coverage, observerdiversity, and temporal consistency predicted professional survey agreement with AUC = 0.884.